PROSES PRODUKSI ALAT ANGKAT KENDARAAN NIAGA KAPASITAS 2 TON - Rio Manoppo; Rudy Poeng; Romels Cresano Apelles Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
The object of this study is the production process of the 2 tonnes capacity lifting equipment commercial vehicle with carried out in manufacture laboratory of the University of Sam Ratulangi. The aim of this study is to build the component, measuring the lifter parts’ processing time, and analyzing the stages of the process, and calculating the production process of the 2 tonnes capacity lifting equipment produced in manufacture laboratory the University of Sam Ratulangi. The result obtained is a commercial vehicle lifting equipment unit manually operated that can do a car lifting till 2 tonnes maximum empty heavy vehicle. The manufacturing time in every single component is 7,684 seconds with 765 units/year production target. Key Word : production process, lifting equipment, production target.